Temperature Effects on Growth Rates and Predation Loss of Bacterial Groups in Marine Ecosystems - ŠESTANOVIĆ, STEFANIJA; VRDOLJAK TOMAŠ, ANA; ŠOLIĆ, MLADEN; ŠANTIĆ, DANIJELA; BOJANIĆ, NATALIA (Mediterranean Marine Science, 2025)
This study investigated the effects of experimental warming on the major bacterial phylogenetic groups in the marine environment, focusing on their growth and grazing rates, phylogenetic community composition and grazing preferences. A series of growth and grazing experiments were performed in microcosms at a temperature increase of 3°C. The growth rates of all bacterial groups were enhanced by temperature increase. SAR11 and Roseobacter were particularly sensitive to temperature changes, while Gammaproteobacteria were the least affected. Protozoan grazing mainly affected fast-growing groups such as Roseobacter and Gammaproteobacteria, while slower-growing groups such as SAR11 were less affected. In most cases, the growth rates of the bacteria increased more with temperature than the grazing rates of predators. This indicates that temperature has a stronger influence on bacterial growth than on predator activity. At higher temperatures the grazing pressure of nanoflagellates (NF) on Roseobacter and Bacteroidetes increased while Gammaproteobacteria were almost exclusively grazed by ciliates (CIL). As a result, the dominant predator of certain groups and the composition of prey changed with temperature increase. The changes in bacterial community composition at higher temperatures were caused both by the direct effect of temperature on bacterial growth and by shifts in predator grazing preferences. Furthermore, our results suggest that bacterial growth and grazing behaviour of bacterial predators do not necessarily occur simultaneously at higher temperatures and highlight the importance of considering bacterial phylogenetic composition when predicting bacterial response to warming.